Blue and UV‐B light synergistically induce anthocyanin accumulation by co‐activating nitrate reductase gene expression in Anthocyanin fruit (Aft) tomato. (15th July 2020) - Kim, M.‐J.; Kim, P.; Chen, Y.; Chen, B.; Yang, J.; Liu, X.; Kawabata, S.; Wang, Y.; Li, Y.
Abstract: The tomato accession LA1996, which carries a dominant allele of anthocyanin fruit ( Aft ) locus, accumulates anthocyanins in the epidermis of fruits when exposed to sunlight. The involvement of blue, UV‐A, UV‐B and a combination of these wavelengths on anthocyanin accumulation and the molecular mechanism of their regulation was investigated in LA1996. The most effective treatment for inducing anthocyanin biosynthesis in Aft fruits was co‐irradiation with blue and UV‐B (blue + UV‐B) light. Finding the correlated genes is an important approach towards understanding their molecular mechanisms. In the present study, the nitrate reductase (NR) gene SlNIA was isolated using RNA‐seq profiling of Aft fruits given different light treatments. The functions of NR‐mediated anthocyanin induction by blue + UV‐B were confirmed using a series of chemical treatments, followed by assessment of NR activity and nitric oxide (NO) detection. The expression of NR was highly induced by blue + UV‐B, and this specificity was also confirmed with the enzyme activity of NR and the NO concentration. The NR inhibitors, which reduce NO generation, the expression levels of anthocyanin related genes and decreased anthocyanin accumulation in LA1996. Our results suggest that NR plays a key role in blue + UV‐B‐mediated anthocyanin accumulation in LA1996 fruits. Abstract : Anthocyanin biosynthesis in response to combined irradiation of blue and UV‐B is dependent by NR activity in Aft tomato fruits.